Does radical cystectomy outperform other bladder preservative treatments in elderly patients with advanced bladder cancer?. Issue 8 (August 2015) - Chen, Chin‐Li; Liu, Chin‐Yu; Cha, Tai‐Lung; Hsu, Chien‐Yeh; Chou, Yu‐Ching; Wu, Sheng‐Tang; Meng, En; Sun, Guang‐Huan; Yu, Dah‐Shyong; Tsao, Chih‐Wei
Abstract : Background : To assess the impacts of age, performance status, and clinical stage on advanced urothelial carcinoma of the bladder (UCB) in patients treated with different treatment modalities. Methods : This retrospective study included 160 patients who underwent radical cystectomy (RC) with/without neoadjuvant or adjuvant chemoradiotherapy, palliative chemotherapy/radiotherapy/chemoradiotherapy (CRT), and transurethral resection of bladder tumor (TURBT) monotherapy for advanced UCB in one institution from 2000 to 2010. Kaplan–Meier analysis was used to calculate the survival distributions of overall survival (OS). The quality of life of the patients was also analyzed. Results : The median age of the patients was 74.0 years, and the mean survival interval was 31.5 months. The 2‐year OS was significantly different among the three modalities [RC > TURBT monotherapy, odds ratio (OR): 1.86, 95% CI: 1.17–2.96, p = 0.009; CRT > TURBT monotherapy, OR: 1.65, 95% CI: 1.06–2.57, p = 0.026]. There were no significant differences in the 5‐ and 10‐year OS rates between the three treatment modalities. Those younger than 76 years receiving RC had a significantly better 2‐year OS than those undergoing CRT and TURBT monotherapy (RC > TURBT monotherapy, OR: 2.38; 95% CI: 1.30–4.33, p = 0.005). The number and duration of re‐hospitalizations were highest in the CRT group and lowest in the TURBT group. Conclusion : The short‐ and long‐term OS rates of the three modalities were similar in those older than 76 years. Therefore, patients younger than age 76 years are likely to have a better outcome undergoing radical cystectomy for advanced UCB.